2020
DOI: 10.1099/ijsem.0.004378
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium canis sp. nov., a novel member of the Bifidobacterium pseudolongum phylogenetic group isolated from faeces of a dog (Canis lupus f. familiaris)

Abstract: A fructose-6-phosphate phosphoketolase-positive strain (GSD1FST) was isolated from a faecal sample of a 3 weeks old German Shepherd dog. The closest related taxa to isolate GSD1FST based on results from the EZBioCloud database were Bifidobacterium animalis subsp. animalis ATCC 25527T, Bifido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…These microorganisms were classified as Gram-positive, nonspore-forming, and nonmotile bacteria that belong to the phylum Actinobacteria [4]. To date, 88 different bifidobacterial (sub)species were classified, mostly isolated from the gastrointestinal tract of numerous animals, the human gut and oral cavity, and insect hindgut [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms were classified as Gram-positive, nonspore-forming, and nonmotile bacteria that belong to the phylum Actinobacteria [4]. To date, 88 different bifidobacterial (sub)species were classified, mostly isolated from the gastrointestinal tract of numerous animals, the human gut and oral cavity, and insect hindgut [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A similar statistically significant trend was found in colony forming units cultivated on WPS-MUP medium intended for bifidobacteria that reached 8.91 ± 1.38 log CFU g -1 in the NWM compared to 7.02 ± 0.93 log CFU g -1 in the OWM (t (50) = 5.87, p = 3.50e-07). In case of FS with lower numbers of bifidobacteria and the presence of clostridia, this medium was not sufficiently selective also allowing the growth of clostridia 51 , 52 . Consequently, a notably greater statistically significant difference was detected between primate parvorders on more selective WSP-NORF medium with bifidobacterial counts of 8.57 ± 2.13 log CFU g -1 for the NWM and 4.32 ± 2.04 log CFU g -1 for the OWM (Z = 5.17, p = 2.38e-07).…”
Section: Resultsmentioning
confidence: 99%
“…They represent nonmotile, anaerobic, nonsporulating, saccharolytic bacteria with a bifid or multiple-branching rod morphology. Currently, the genus Bifidobacterium comprises 94 taxa, representing 82 species and 12 subspecies [4][5][6][7][8][9][10][11][12] (Table 1). In recent years, the phylogeny of the Bifidobacterium genus has been explored using different methods based on the sequencing of the 16S rRNA gene, by means of a multilocus approach, or the sequencing of several housekeeping genes (i.e., clpC, dnaJ, rpoC, xpf, dnaB, and purF) [13,14].…”
Section: History and Taxonomy Of Bifidobacteriamentioning
confidence: 99%
“…Bifidobacteria also naturally occur in the gastrointestinal tract (GIT) of animals, such as nonhuman mammals, insects, and birds [5][6][7][8][9][10][11], while they have also been isolated from human blood [51], sewage [42], the oral cavity [55], and fermented milk [15]. In this context, it has been demonstrated that the ability of bifidobacteria to adapt to specific environments is species-dependent [4].…”
Section: Ecology Of Bifidobacteriamentioning
confidence: 99%